Emerging Pharmaceutical Therapies to Address the Inadequacy of a Gluten-Free Diet for Celiac Disease - Martina Crepaldi; Michela Palo; Daria Maniero; Luisa Bertin; Edoardo Vincenzo Savarino; Robert P. Anderson; Fabiana Zingone (Pharmaceuticals, 2023)
Celiac disease (CeD) is a chronic autoimmune disorder triggered by the ingestion of gluten, affecting around 1% of the global population. It is a multifactorial disease involving both genetics and environmental factors. Nowadays, the only available treatment for CeD is a life-long gluten-free diet (GFD), which can cause a significant burden for patients, since symptoms and mucosal injury can persist despite apparent compliance with a GFD. This could also lead to psychological consequences and affect the quality of life of these patients. Thankfully, recent advances in understanding the pathogenesis of CeD and the availability of various targets have made it feasible to explore pharmaceutical treatments specific to CeD. Recently, the FDA has highlighted the unmet needs of adult patients on a GFD who experience ongoing symptoms attributed to CeD and also show persistent duodenal villous atrophy. This review will outline the limitations of a GFD, describe the targets of potential novel treatment of CeD and provide an overview of the primary clinical trials involving oral and injectable agents for a non-dietary treatment of CeD.